The Influence of Parents, Coaches, and Peers in the Long-Term Development of Highly Skilled and Less Skilled Volleyball Players - Coutinho, Patrícia; Ribeiro, João; da Silva, Sara Mesquita; Fonseca, António M.; Mesquita, Isabel (Frontiers in Psychology, 2021)
The purpose of this study was to understand the perceptions of highly skilled and less skilled volleyball players about the influences that parents, coaches and peers had on their sport development and performance achievement. Highly skilled (n=30) and less skilled (n=30) volleyball players participated in semi-structured retrospective interviews to explain how parents, coaches and peers may have influenced their sport participation. Data was analyzed through a process of content analysis. Results indicated that parents, coaches and peers had an important influence in player’s sport development but differing according to players’ expertise level. Concerning to parental influences, tangible support during the early years of development was mentioned by all players. However, parents’ level of involvement and parenting styles revealed interesting differences between highly skilled and less skilled players. Highly skilled players perceived a moderate parental involvement and an autonomy-supportive parenting style, while less skilled players referred a parental excessive involvement in players’ sport participation. Coaches influences showed to have some similarities in the early years with all players mentioning coaches as caring and recognizing their value as an athlete. However, highly skilled players described a different training environment characterized by a demanding coach, individualized instruction and specific goal setting. Regarding peers’ influence, all players recognized that friends were not only one of the main reasons to start playing volleyball, but also an important source of support to still engaged and staying motivated to do sport. Highly skilled players, however, were the only that mentioned the importance of teammates’ positive push and critics during practice for enhancing their motivation, team cohesion and friendship. They also highlighted the importance of friends outside of sport in the later years of their career by acting as an escape from all the pressure that emerged from volleyball training and competition demands. Overall, these findings highlight different social influences according to the players’ expertise level suggesting the need to examine more extensively the nature of significant others’ support on athlete and talent development.